Correct selection of the ORC system parameters for the exhaust gases heat source - Grzebielec, Andrzej; Rusowicz, Artur; Ziąbka, Tomasz (International Conference “Environmental Engineering”, 2020)
Contrary to appearances, ORC (Organic Rankine Cycle) systems should not be selected for the highest available temperature of the upper heat source. This approach allows, of course, to achieve the highest energy efficiency, but this happens at the expense of the electrical power obtained. This solution would be good for an infinite heat source. In practice, there is always a finite heat source power. Therefore, the analysis should take into account other aspects than just maximum efficiency. The article presents a method of selecting ORC system parameters for a heat source in the form of waste gases, enabling the highest electrical power to be obtained. The analysis shows that even a significant reduction in the evaporation temperature of the working medium in the ORC system compared to the source temperature is beneficial for the profitability of investing in an ORC system. The analysis showed that for flue gases with temperatures of 300, 400, 500 and 600 °C, the best evaporating temperatures of the working medium in the ORC system are 145 °C, 185 °C, 214 °C and 250 °C, respectively. The highest level of generated electricity is obtained for these temperatures.
Keywords: ORC; energy efficiency; ORC working parameters; waste heat; exhaust gases; reduction of CO2 emissions